EMPOWERING COMMUNICATION GOALS IN SDGs CLIMATE ACTION WITH ANCHORING TECHNIQUE: A LINGUISTIC APPROACH - Angelica Laurina Silaban; Grace Yolanda Panjaitan; Rita Hartati (ADISAM Publisher, 2025)
In the digital era, effective communication is crucial for advancing climate action within the framework of the Sustainable Development Goals (SDGs). This study examines the application of anchoring strategy techniques through a linguistic approach to enhance climate change communication. By analysing digital content such as social media posts, videos, and captions the research identifies the impact of comparative, basic, counter, and debiasing anchoring strategies on audience engagement. Quantitative analysis of interactions (likes, comments, and shares) reveals that strategic semantic framing, persuasive discourse, and pragmatic language use significantly improve message clarity and foster a sense of collective responsibility. The findings suggest that leveraging these linguistic techniques can bridge existing communication gaps, motivate proactive climate behaviour, and support more effective climate action. Future research should explore additional linguistic methods to further refine communication strategies across diverse audiences.